2018
DOI: 10.1016/j.pcd.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lifestyle changes on adults with prediabetes: A systematic review and meta-analysis

Abstract: Lifestyle intervention is an efficacious, safe, and cost-effective measure to reduce the risk of progression to type 2 diabetes in people diagnosed with prediabetes. More research is necessary to compare the efficacy of various modes, frequencies, and intensities of lifestyle intervention across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 79 publications
(282 reference statements)
0
98
0
3
Order By: Relevance
“…Focusing on the group restricted to adults with prediabetes, it is not clear why they do not seem to reap any benefits from meeting MVPA or having lower levels of sedentary behavior. It is possible that individuals with prediabetes who maintained a high level of MVPA at V1 and at V2, may have slowed their progression to diabetes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the group restricted to adults with prediabetes, it is not clear why they do not seem to reap any benefits from meeting MVPA or having lower levels of sedentary behavior. It is possible that individuals with prediabetes who maintained a high level of MVPA at V1 and at V2, may have slowed their progression to diabetes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of this condition provides a window of opportunity to alter the natural history of T2DM. Several DM prevention programs have identified lifestyle interventions that potentially provide sustained benefits for many years, with a lower rate of progression from pre-diabetes to T2DM [52]. Our estimate identified 47.3% of the screen-positive dental patients were identified as pre-diabetic with the reference standard.…”
Section: Poc Screening Test Outcomementioning
confidence: 80%
“…5 If more clinicians recognised the presenting symptoms of gastrointestinal dysmotility and absence of tears in infancy as potentially associated with multiple endocrine neoplasia type 2B, more children could undergo age-appropriate thyroidectomy, which has been shown to improve survival in hereditary medullary thyroid cancer. 6 First-line treatment for phaeochromocytoma in patients with multiple endocrine neoplasia type 2B is adrenalectomy. Historically, this procedure has been total adrenalectomy although recent surgical advances have led to the increasing use of adrenalsparing procedures; before this study, outcomes of adrenal-sparing surgery had not been reported specifically in multiple endocrine neoplasia type 2B.…”
Section: Careful Investigation Of a Rare Disease: Insights Into Multimentioning
confidence: 99%
“…First, lifestyle interventions within their current form (ie, increasing physical activity, healthy dietary habits, and weight loss) can reduce the progression to diabetes in people with IGT. 6 However, such interventions do not appear to reduce diabetes incidence in those with IFG, [7][8][9] which is different in terms of pathophysiology from IGT. 10…”
mentioning
confidence: 99%